FERTILISATION SOURCE AND DOSE OPTIMISATION BOOST YIELD OF DURUM WHEAT IN MEDITERRANEAN CLIMATIC CONDITIONS - Mazlum AYHAN; Ferhat KIZILGEÇİ; Muhammad Aamir IQBAL (Journal of Applied Life Sciences and Environment, 2021)
Climate change, global warming, environmental pollution, greenhouse gas emissions from agricultural fields, stagnant wheat yields and reduced farm economic returns require optimisation of sources and doses of plant nutrients. A field study was conducted to evaluate wheat response to different forms of fertilisers and nitrogen (N) doses under Mediterranean conditions. The field trial was comprised of fertiliser sources, including chemical fertilisers, compost and leonardite, while different nitrogen levels (0, 80, 160, 240 kg ha-1) were also tested. The experimental variables included yield attributes (height of the, length of the spike, spikelets number per spike, thousand-grain weight and grain yield). In addition, nutritional quality attributes like protein and starch contents were studied along with NDVI values of wheat under different fertilisation regimes. The trial was executed using a randomised complete block (factorial) design using four replications. The results revealed that fertiliser forms and N doses remained ineffective for boosting yield attributes of wheat. For nutritional characteristics of wheat grains, a higher N dose remained instrumental in boosting protein, starch and wet gluten contents. Thus, 240 kg ha-1 of N dose might be recommended for general adoption under Mediterranean conditions; however, study findings are limited in scope and further in-depth studies are needed by testing organic manures from plant and animal origins.